Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) di SD dan SMP Kecamatan Kapuas Tengah - Hamidah, Noor; Santoso, Mahdi; Silaen, Cindy Claudia Br; Hasanah, Siti Fadillah; Zaini, Akhmad; Pramana, Andika; Sulistiawati, Putri; Ningrum, Faradita Ersanti (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2024)
School-age children are classified as a critical age group, because at that age an individual is more susceptible to experiencing health problems. The health problems experienced by school-age children are very complex and varied, but according to many children who are sick today because of a lack of knowledge about personal hygiene. Socialization regarding the application of Clean and Healthy Living Behavior to students is a response to problems that occur which is carried out in order to increase students' awareness and knowledge so they can practice Clean and Healthy Living Behavior. This outreach was carried out to students of SDN 1 Masaran and SMPN 5 Kapuas Tengah, in Masaran Village, Kapuas Tengah District, Kapuas Regency, Central Kalimantan Province. The implementation method uses a qualitative method to identify the Clean and Healthy Lifestyle of school children at the elementary and junior high school levels. The activity was carried out in two stages, namely planning and implementation through lectures, questions and answers, and hand washing demonstrations. The PHBS socialization activities went smoothly and well, all students enthusiastically took part in the socialization activities regarding PHBS. The results of the service include an increase in students' knowledge regarding PHBS which is proven through the understanding of PHBS and the implementation carried out by students